On the Quasi-Stationary Solutions in 1 D Non-hermitian Systems - Fernández, Francisco Marcelo (2023)
In this paper we show that some 1 non-Hermitian lattices can be easily transformed into Hermitian ones. This fact clearly facilitates the analysis of the former. Our theoretical results suggest that the results and conclusions derived earlier by other authors may not be correct.